Strategies of Entrepreneurs with Disabilities in Sustaining and Growing Their Business: Contributions to Achieving the Sustainable Development Goals - Yashinta Putri Dwi Astuti; Deva Nita Mulya; Aldian Umbu Tamu Ama (International Journal of Entrepreneurship and Sustainability Studies, 2025)
Entrepreneurship represents a viable option for persons with disabilities as it offers opportunities to accommodate their needs, build independence, determine their work patterns, avoid discrimination, foster personal development, and contribute positively to the lives of others. Thus, Entrepreneurs with Disabilities (EWDs) play a significant role in realizing the commitments of the Sustainable Development Goals (SDGs), particularly in achieving inclusive and sustainable economic growth, employment opportunities, and decent work for all. This study aims to explore the sustainable strategies adopted by “Kopi Hening” to maintain business continuity. The research is exploratory in nature and adopts a qualitative approach to obtain an in-depth understanding of the “Kopi Hening” phenomenon. Data were collected through data triangulation, which involved interviews, observations, and documentation. The data were analyzed inductively to derive emerging themes, and their validity was ensured through triangulation and member checks to enhance the credibility and trustworthiness of the findings. The findings reveal that the strategies include external support, self-development, a sense of ownership, uniqueness, product evaluation, partnership, and effective financial management. Facilitators play a crucial role in supporting the sustainability of EWDs, as it has been noted that EWDs greatly depend on external support. However, this study has limitations, as it is based on a case study and needs more diverse EWD respondents. Future research should expand the number of respondents by involving the government. Additionally, future studies could focus on the role of applied technology in supporting EWDs, particularly deaf individuals, to address communication barriers through technological solutions.